THE USE OF FERMENTED COCONUT MEAL (Cocos nucifera) USING EM4 IN FEED ON THE GROWTH OF GURAMI FISH (Osphronemus gouramy) - Annisa Meliana; Niken Ayu Pamukas; Indra Suharman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Copra meal flour is used as a fish feed ingredient with a fairly high protein content of 18–24%. However, its crude fiber content is high, which can reduce its digestibility. Therefore, fermentation is needed to improve the quality of copra meal. This study aims to determine the percentage of copra meal flour fermented with EM4 in feed to produce the best feed efficiency and growth of gorami fish. This study employed an experimental method with a completely randomized design (CRD). Five types of feed were formulated to contain 32% protein, with feed P0 containing 100% soybean meal (control feed), and feeds P1, P2, P3, and P4 replacing soybean meal with fermented copra meal at 25%, 50%, 75%, and 100%, respectively gorami fish fry (with an average body weight of 2.08 ± 0.11 g) were stocked in floating net cages measuring 1 × 1 × 1 m3 at a density of 25 fish per cage. The experimental feed was given at 10% of the test fish biomass frequency three times a day at 08.00, 12.00, and 16.00 WIB, for 56 days. Feed digestibility was measured by giving the test feed three times a day to satiation, mixed with Cr2O3 and protein. The results showed that the use of TBKF in the feed significantly improved feed efficiency and gorami fry growth. Based on the results, it can be concluded that the use of 75% fermented copra meal can replace soybean meal in gorami feed, with feed digestibility (57.63%), protein digestibility (80.08%), protein retention (37.56%), feed efficiency (52.31%), and specific growth rate (4.05%).